Pemberdayaan Masyarakat Desa Jambu Melalui Dialog Terpadu: Sinergi Penguatan Ekonomi Dan Pencegahan Pernikahan Dini - Nailah Farah; Dwi Alma Putri Azahra; Fatimah Muthmainah; Febri Tul Syahdia; Faiz Mubarok; Dwi Alya Berliana; Muhammad Akbar Amanta; Ifrohati (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
Early marriage and economic vulnerability are two closely related structural problems in rural areas. In Jambu Village, the community's dependence on the seasonal agricultural sector often encourages the decision to marry off children at a young age, especially after graduating from Junior High School (SMP), as a shortcut to reduce the family's financial burden. This community service activity aims to break the chain of these problems through an integrated dialogue approach. The activity was held at the Jambu Village Head Office, Gelumbang District, Muara Enim Regency on January 25, 2026, involving around 50 participants consisting of teenagers, parents, and community figure representatives. The method used was Community Education through socialization and interactive consultation. The results of the activity showed a significant increase in community understanding regarding the destructive impact of early marriage from health, psychological, and educational aspects. In addition, residents gained new insights regarding family financial management and the utilization of plantation potential as an independent home business opportunity. This activity concludes that preventing child marriage is not enough just with moral prohibitions but must be accompanied by the provision of family economic readiness and independence